Cirebon Language Revitalization In Cirebon City through Cirebon Language Learning - Nuniek Setya Sukmayani; Emzir Emzir; Sabarti Akhadiah (STKIP Singkawang, 2017)
Law of the Republic of Indonesia no. 4 Year 2009 about the language states that the local government must develop, foster, and protect the local languages and literature in order to continue to fulfill their position and function in the life of society in accordance with the development of the era performed gradually, systematically and sustainably by local governments under the coordination of linguistic institutions, and to remain part of Indonesia's cultural treasures. Based on the Cirebon preliminary observation result, it is threatened with extinction because its speakers are fewer and rarely even do not use Cirebon language in their daily intercourse, although in the last few years there are lessons in Cirebon - Dermayu. This is because the lesson is just as a science. That is, even though the learners’ report is good value, eg 9 (nine), but in the daily association does not use Cirebon language. Therefore, researchers intend to examine the Cirebon language with the title - Cirebon Language Revitalization Through Cirebon Language Learning. This research generally aims to obtain a deep picture and understanding of Cirebon language revitalization in Cirebon City, while its long-term goal is to obtain findings about efforts to preserve the Cirebon language in order to remain functional for life in the city of Cirebon in the midst of the widespread use of Language Indonesia as the national language in the country of the Republic of Indonesia, so as to assist the government in developing, fostering and protecting local languages and literature in accordance with the laws described above. The method used in this research is Ethnography with Spradley research procedure. The results of this study are expected to be a reference in improving the textbook Language Cirebon and refine the policy to preserve the language of Cirebon in order to explore the noble values of local wisdom it contains.